Knockdown of CircCRIM1 Inhibits HDAC4 to Impede Osteosarcoma Proliferation, Migration, and Invasion and Facilitate Autophagy by Targeting miR-432-5p - Liu J; Feng G; Li Z; Li R; Xia P (Cancer Management and Research, 2020)
Jun Liu,1 Guang Feng,2 Zhengwei Li,3 Rui Li,1 Peng Xia1 1Department of Hand Surgery, The Second Hospital of Jilin University, Changchun, Jilin 130000, People’s Republic of China; 2The Fourth Medical Center of PLA General Hospital, Beijing 100048, People’s Republic of China; 3Department of Orthopaedics, The Second Hospital of Jilin University, Jilin 130000, People’s Republic of ChinaCorrespondence: Peng XiaDepartment of Orthopaedics, The Second Hospital of Jilin University, No. 218 Ziqiang Street, Nanguan District, Changchun 130000, Jilin Province, People’s Republic of China, Tel +86-043181136193Email puonmx@163.comBackground: Circular RNAs (circRNAs) serve for a genre of considerable modulatory molecules that have been largely researched in human cancers. However, the contribution of circRNA cysteine-rich transmembrane bone morphogenetic protein regulator 1 (circCRIM1) to osteosarcoma (OS) is completely unclear.Methods: All the RNA levels were examined via quantitative real-time polymerase chain reaction (qRT-PCR). Cellular proliferation and migration/invasion were, respectively, analyzed using 3-(4, 5-dimethylthiazol-2-y1)-2, 5-diphenyl tetrazolium bromide (MTT) assay and transwell assay. The determination of all protein expression was administrated by Western blot. Dual-luciferase reporter assay was used for proving the target combination. The exploration of circCRIM1 in vivo was performed by xenograft assay.Results: In OS tissues and cells, circCRIM1 was differentially up-regulated. Functionally, cell proliferation, migration and invasion were suppressed while autophagy was promoted after circCRIM1 was down-regulated in OS cells. Mechanistically, mircoRNA-432-5p (miR-432-5p) was a miRNA target of circCRIM1 and the inhibitory effect of circCRIM1 knockdown on OS progression was achieved by targeting miR-432-5p. Moreover, histone deacetylase 4 (HDAC4) was a downstream gene of miR-432-5p and circCRIM1 targeted miR-432-5p to up-regulate HDAC4 level. MiR-432-5p inhibited proliferation, migration, and invasion but enhanced autophagy of OS cells through down-regulating HDAC4. In vivo, knockdown of circCRIM1 decreased OS growth via acting on the miR-432-5p/HDAC4 axis.Conclusion: Our findings elucidated the oncogenic function of circCRIM1 in OS via the regulation of the miR-432-5p/HDAC4 axis, affording a novel view about how circRNA participated in OS development.Keywords: circCRIM1, osteosarcoma, miR-432-5p, HDAC4